Al-Khawarij dan Al-Murjiah: Sejarah dan Pokok-Pokok Ajarannya - Almahdali, Sayyid Syahdan; Jafar, Usman; Santalia, Indo (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study delves into the definitions and historical emergence of two early Islamic sects, al-Khawarij and al-Murjiah, and contrasts their core teachings. Al-Khawarij, derived from the term "kharijah," signifying rebellion, formed after a faction of Ali bin Abi Talib's followers ended up disagreeing with his decision to arbitrate during the Battle of Siffin. This group believed that any deviation from divine will was unacceptable, thus condemning arbitrations like those accepted by Ali. On the other hand, al-Murjiah, from the root "Irj?’," meaning deferral, emerged as a response to the religious and political fragmentation in early Islam. This group proposed that faith alone suffices for salvation, detaching actions from faith and delaying judgment for grave sins to the Last Day. Through historical analysis, this paper examines the socio-political dynamics that led to the rise of these factions and their lasting impact on Islamic jurisprudence, theology, and community cohesion.